2017
DOI: 10.5005/jp-journals-10024-2003
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Glow Discharge as a Mode of Disinfection for Elastomeric Impression Materials

Abstract: Introduction: Prosthodontic practice involves procedures in which impressions of the maxillary and mandibular arches are mandatory. Cross infection is one of the major problems that can occur in regular dental practice. Every dentist should take utmost care to prevent cross infection as oral cavity is the source of variety of microorganisms which can often cause diseases that can be fatal. Although precautions, such as wearing of gloves and mask, sterilization of instruments are given importance, the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…[ 3 4 5 ] Dentists and supporting dental personnel are exposed to a variety of microorganisms that may lead to infectious diseases, such as acquired immunodeficiency syndrome, hepatitis B, tuberculosis, and herpes I and II. [ 6 ] Transmission of these diseases occurs due to contact with blood and other body fluids, while performing dental procedures and handling contaminated instruments and impressions. [ 7 8 ] Various studies have shown that handling contaminated dental impressions, as well as the stone casts poured from them, can lead to infections.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 5 ] Dentists and supporting dental personnel are exposed to a variety of microorganisms that may lead to infectious diseases, such as acquired immunodeficiency syndrome, hepatitis B, tuberculosis, and herpes I and II. [ 6 ] Transmission of these diseases occurs due to contact with blood and other body fluids, while performing dental procedures and handling contaminated instruments and impressions. [ 7 8 ] Various studies have shown that handling contaminated dental impressions, as well as the stone casts poured from them, can lead to infections.…”
Section: Introductionmentioning
confidence: 99%